Dynamics of a Fractional Order Eco-Epidemiological Model - Kartika Nugraheni; Trisilowati Trisilowati; Agus Suryanto (Journal of Tropical Life Science, 2017)
In this paper, we propose a fractional order eco-epidemiological model. We considere the existence of time memory in the growth rate of the three populations. We observed the dynamical behaviour by analysing with fractional order and then simulateing using Grünwald-Letnikov approximation to support analytical results. It found that the model has five equilibrium points, namely the origin, the survival of susceptible prey, the predator free equilibria, the infected prey free equilibria, the interior equilibria. Numerical simulations show that the existence of fractional order  is a factor which affects the behaviour of solutions.